Dari Ekoteologi ke Ekospiritualitas Rekonstruksi Kesadaran Ekologis Masyarakat Adat Benawas di Rimba Kobar - Dismas Kwirinus; Raymundus I Made Sudhiarsa; Robertus Wijanarko; Mikael Dou Lodo (Kamaya: Jurnal Ilmu Agama, 2026)
This research examines the conceptual transformation from ecotheology to ecospirituality in reconstructing the ecological consciousness of the Benawas Indigenous community in Rimba Kobar. The study aims to identify how theological values rooted in human–nature relations evolve into more holistic, contextual, and experientially grounded spiritual practices. Employing a qualitative approach with an ethnographic method, data were collected through participant observation, in-depth interviews, and narrative analysis of cultural practices and indigenous rituals. The findings reveal that the Benawas community perceives nature not merely as a creation to be theologically preserved, but as a sacred entity intrinsically embedded in their spiritual lifeworld. This transformation is marked by a shift from a normative-doctrinal framework toward an immanent, relational, and sustainability-oriented spiritual experience. The emerging ecospirituality reinforces an ecological ethic grounded in local wisdom, contributing to environmental preservation and resilience. This study underscores the importance of integrating theological and spiritual dimensions in addressing contemporary ecological crises, while offering an alternative perspective rooted in indigenous knowledge systems for advancing the discourse on religious ecology.